OPTIMIZING POPULATION ADMINISTRATION SERVICES IN RURAL AREAS: A STUDY OF DIGITAL INTEGRATION AND BUREAUCRATIC RESPONSIVENESS IN BUNGA VILLAGE - Sri Wahyuni Ismail; Mohamad Ikbal Kadir; Ikram Muhammad (Journal of Economic, Business, and Administration (JEBA), 2024)
Population administration is a fundamental public service that ensures citizens' legal identity and access to social protection. This study aims to evaluate the implementation of population administration services in Bunga Village, Bone Raya Sub-district, Bone Bolango Regency, focusing on the integration of the Population Administration Information System (SIAK) and the quality of frontline service delivery. Using a qualitative descriptive approach, data were collected through in-depth interviews with village officials and community members, field observations, and documentary analysis. The findings reveal that Bunga Village has successfully modernized its administrative workflow through SIAK, enhancing data accuracy and processing efficiency. A key highlight is the village's "zero-cost" policy, which ensures inclusive governance and equitable access for all residents. However, the study identifies a significant "digital divide" characterized by unstable network connectivity, which hampers real-time online operations. To mitigate this, village officials adopt a proactive "manual bypass" strategy by physically delivering documents to the Public Service Mall (MPP). The study concludes that while technological adoption is vital, human-centric bureaucratic responsiveness remains the primary driver of service quality in resource-constrained rural environments. Continuous infrastructure improvement and professional staff training are recommended to sustain these administrative advancements.